Prevention of Chlamydia Infections With Theater in School Sex Education. (June 2020) - Jerlström, Charlotta; Adolfsson, Annsofie
The aim of the study was to evaluate if an intervention including theater in school sex education affects students' knowledge, attitudes, and behavior regarding condom use in Sweden. The study was a cluster randomized controlled trial. The intervention group got a play, value exercises, chlamydia games, condom school, and interactive replay with professional actors and staff from a youth guidance center. The control group got standard sex education from school staff. Students in both groups answered web surveys on knowledge, attitudes, and behavior regarding condom use. Posteducation, knowledge on condom use, chlamydia, and protection had increased in both groups. However, students in the intervention group showed higher levels of knowledge, improved attitudes, and less risky behavior in regard to condom use compared to the control group. The intervention titled SAFETY seemed to be a beneficial supplement to standard sex education and more effective with regard to knowledge of condom use.